Medición y propuesta de mejoramiento del clima laboral en una empresa pública, durante el periodo de abril 2016 a febrero 2017. - Orbe Calvachi, Gabriela de los Ángeles (2017)
In the last decade organizations have had a significant development characterized by the improvement of their processes, inclusion of technology and the hiring of people with greater competencies, so that the study of organizational climate acquires a growing interest in organizations. From the organizational model based on human resources management, proposed by authors like Fayol and Taylor, it evolved to a human talent management that gives importance to people not only as resources but as those capable of achieving objectives and directing the future Of the organization through their interpersonal relationships and links, attitudes, behaviors and reactions of the world of work. The public company referred to in this project has the need to measure its work climate with the aim of improving the work environment by increasing productivity and avoiding staff turnover. The evaluation of the work environment was done through a quantitative methodology, based on a survey with measurement of 8 factors: customer orientation, leadership, working conditions, work motivation, identification with the organization, interpersonal relationships, communication and collaboration; Determined from the initial diagnosis. The application of the survey resulted in a low index, explaining the conditions that should be improved. In the future we hope to work on improving the work environment by focusing on specific activities to mitigate problems of interpersonal relationships, the context in which they develop and the structure of the organization.